TEACHER TRAINING IN MATHEMATICS IN BRAZIL - Kapron, Tadeu; Erinalva Bezerra de Oliveira, Maria (Revista Gênero e Interdisciplinaridade, 2025)
This article aims to briefly describe some essential aspects for the training of Mathematics teachers for Basic Education, taking into account the expected profile for the commitment to the development of the integral subject. The training in Mathematics is based on providing the future teacher with mastery of the conceptual field of mathematics historically produced. The transformations involving education specifically seek the formation of the integral subject, and the school is a social environment that seeks preferably to provide scientific knowledge to the student, a place where technology has historically contributed significantly to the improvement and construction of knowledge. Without it, the essence of many concepts would be impossible to be explored in a concrete and objective way. It is necessary for the teacher to know how the student learns and to have the ability to monitor their process of acquiring this knowledge. Investing in technology is investing in knowledge, accessibility, quality of life and the development of new skills, therefore, in the 21st century there is no way for an education professional to distance themselves from this necessary process that is present in people’s lives. Mathematics teaching in Brazil is undergoing movements and trends that are increasingly concerned with the quality of learning and follows different ways of stimulating the appropriation of knowledge, stimulating the development of thought and the construction of new skills. Digital technologies, as they are present in everyday life, can be explored in schools. However, there are still great difficulties in offering conditions in schools (mainly public schools) that encourage teachers to work with digital educational resources.